"I am not a Good Woman?" Exploring the Views and Challenges of Nurses When Discussing HPV Testing and Associated Cervical Screening with Women in Iraq - Suhailah M. Ali; Rebecca Lawes; Ayla Khedher Ghalib (SAGE Publishing, 2023)
Introduction Cervical cancer is mostly caused by high-risk Human papillomavirus HPV, with an estimation prevalence of HPV of 99.7% worldwide. The US Food and Drug Administration (FDA) approved an HPV test for primary cervical screening in 2014. An HPV-DNA test, which provides higher protection against invasive cervical carcinomas, is replacing the long-standing Pap smear as the primary method of cervical cancer screening. Objective To explore nurses' experience and knowledge of HPV DNA testing and how screening impacts on women's health through increasing awareness and proposing actions for health education strategies. Method A qualitative exploratory study was conducted on a purposeful sample of 25 qualified nurses, who were all employed in regional hospitals within a gynecological department in Kirkuk, Iraq. The nurses were interviewed with a semi-structured topic guide between November 2021 and February 2022. Responses were transcribed verbatim, translated into English and analysed using a content thematic analysis approach. Results Four themes with associated sub-themes emerged following coding and peer review. Participants had lack of experience and fragmented knowledge of HPV DNA testing/screening. Culturally sensitive resources for patients and training for nurses was identified key requirements. Conclusions Currently, there are no facilities for a HPV testing/screening services available in Iraq. The role of nurses undertaking HPV screening is not established and yet nurses represent the largest sector of health professionals. The dissemination of a collaborative HPV screening training programme to include clinical competence and knowledge for nurses and gynaecologists may improve knowledge, and could also be effective in improving patient awareness and engagement with cervical health.